Potatisen ur ett handelsperspektiv - Boredahl, Annika (2008)
The potato has had an important role in the Swedish dietary customs for quite some time. However, during the last forty years, consumption has decreased from 87 kg/year and person to 46 kg/year and person. Other products such as pasta, rice and bulgur are competing with the potato. Many of the competitors have been developed and refined while the potato has not changed much. The potato is still a bulk product while competing products have been differentiated. Stakeholders within the potato market has realized that something has to be done and today there are a number of organizations and networks that all actively work to preserve the Swedish agriculture and specifically the potato as a product. The purpose with this essay is to examine how store managers in the Swedish grocery stores view the handling of the potato in the store, the quality and packaging, marketing and future consumption. The objective is to find out some recommendations or ideas that the organisation Svensk Potatis, can use to develop the potato as a product that is adapted to the trade and the consumers´ needs. Ten phone interviews with staff in charge of produce in grocery stores where done. The stores where chosen according to market shares and the interview subjects where given fifteen questions, and the replies where then analyzed. The result show that half of the respondents believe that the potato consumption will decrease in the near future. It also shows that a development of the product is necessary while the consumer asks for alternative potatoes that take short time to prepare. The background in the essay is a collaboration between Lena Andersson and Annika Boredahl. (Lena Andersson has focused on the consumer while Annika Boredahl focused on the grocery store.)